Influence of operating conditions and membrane fouling on water flux during seawater desalination using air gap membrane distillation - Hung, Duong Cong; Nguyen, Huynh Thai; Thao, Pham Manh; En, Trinh Thi; Son, Luong Trung (Vietnam Journal of Chemistry, 2017)
Membrane distillation (MD) has emerged as a promising process for seawater desalination applications to augment fresh water supply in remote coastal areas. Amongst four basic MD configurations, air gap membrane distillation (AGMD) exhibits the highest thermal efficiency, and thus is the most used configuration for small-scale seawater desalination. In this study, the influences of operating conditions and membrane fouling on water flux of a lab-scale AGMD process with actual seawater feed were systematically investigated. The experimental results demonstrated strong impacts of feed temperature, circulation rates, and membrane fouling on the process water flux. Increasing feed temperature exponentially raised water flux but also aggravated polarization effects of the AGMD process. Elevating water circulation rates, particularly of the feed stream, helped alleviate polarization effects, hence improving the process water flux. During the AGMD process of raw seawater feed, the accumulation of organic matters on the membrane reduced its active surface for water evaporation, increased polarization effects, and therefore significantly reduced the process water flux. Pretreatment of the seawater feed by 0.45 mm paper filters removed organic foulants from the feed, and hence helped sustain the water flux of the AGMD process at water recoveries up to 70 %. When the process water recovery exceeded 70 %, water flux rapidly dropped owing to the precipitation of sparingly soluble salts (e.g. CaSO4, CaCO3) on the membrane. Subsequent cleaning the fouled membrane using vinegar removed nearly all foulants from the membrane surface to restore the membrane hydrophobicity, and thus the process water flux. The results reported in this study manifest that seawater AGMD desalination can be a practical process to supply drinking water to small and remote communities in Vietnam. Keywords. Membrane distillation (MD), air gap membrane distillation (AGMD), seawater desalination, membrane fouling, membrane fouling mitigation.